Macroeconomic Determinants of Consumption Inequality in Nigeria: Does Agricultural Productivity Matter? - Oziengbe Scott Aigheyisi; Presley Kehinde Osemwengie (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
The paper examines the effect of agricultural productivity and other macroeconomic variables on consumption inequality in Nigeria. The ARDL approach to cointegration and error correction modeling was employed for the analysis. The study found that agricultural productivity and domestic investment reduce consumption inequality in the long run. FDI was also found to be associated with reduction in consumption inequality in the short run, but its long run effect was not statistically significant. Based on the evidence, the study recommends as measure to reduce consumption inequality in the country, increased investment in the agriculture sector to enhance its productivity, and improvement in the investment environment through infrastructural development, including energy, road, telecommunication infrastructure, favourable, tax policies, enhanced national security, etc. to encourage domestic investment and enhance the attractiveness of the economy to FDI.